Interaction of Estradiol and Endoplasmic Reticulum Stress in the Development of Esophageal Carcinoma - Wang, Chen; Wang, Peng; Liu, Jun-Chao; Zhao, Zhen-Ao; Guo, Rui; Li, Ying; Liu, Ya-Sen; Li, Shu-Guang; Zhao, Zi-Gang (Frontiers in Endocrinology, 2020)
Gender differences in esophageal cancer patients indicate estradiol may have anti-tumor effects on esophageal cancer. The initiation of endoplasmic reticulum stress (ERS) can induce apoptosis in esophageal cancer cells. However, it is still unknown whether estradiol inhibits the development of esophageal cancer by activating ERS pathway. In this study, the gender difference in the development of esophageal cancer was observed by analyzing clinical data and the experimental tumor xenografts in mice. Meanwhile, we investigated the mechanism of ERS in estradiol-mediated inhibition of esophageal cancer using esophageal squamous cell carcinoma cell line EC109. The proportion of male patients with esophageal cancer was significantly higher than female patients. Meanwhile, male patients were prone to have adventitial invasion. The weight of transplanted tumors in female mice was significantly smaller than male mice. In vitro experiments showed estradiol inhibits the viability and migration of EC109 cells by increasing the expression of ERS-related proteins, whereas ERS inhibitor 4-PBA abolished the effects of estradiol. In conclusion, our data demonstrate sex difference exists in the occurrence of esophageal cancer. Estradiol can inhibit the viability and migration of esophageal cancer cells through the activation of ERS, providing a novel insight for esophageal cancer development, treatment and prevention.